2019
DOI: 10.1186/s40478-019-0746-y
|View full text |Cite|
|
Sign up to set email alerts
|

Total copy number variation as a prognostic factor in adult astrocytoma subtypes

Abstract: Since the discovery that IDH1/2 mutations confer a significantly better prognosis in astrocytomas, much work has been done to identify other molecular signatures to help further stratify lower-grade astrocytomas and glioblastomas, with the goal of accurately predicting clinical outcome and identifying potentially targetable mutations. In the present study, we subclassify 135 astrocytomas (67 IDH -wildtype and 68 IDH -mutant) from The Cancer G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 48 publications
(70 reference statements)
3
61
1
Order By: Relevance
“…The presence of DM is a poor prognostic factor in various cancer types. Concordant with our observations, several studies have reported that the high level of copy number alteration is significantly associated with poor survival and outcomes in various cancer types, including primary prostate, breast, endometrial, pancreatic, and colorectal cancer [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…The presence of DM is a poor prognostic factor in various cancer types. Concordant with our observations, several studies have reported that the high level of copy number alteration is significantly associated with poor survival and outcomes in various cancer types, including primary prostate, breast, endometrial, pancreatic, and colorectal cancer [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…But the frequencies of mutations in MIBC patients are overall high, it is not surprising that the differences were not obvious among patients with different infiltrating TMEs. CNVs are duplications or deletions of continuous base pairs of genes, and several studies have found that higher frequencies of CNVs always predict a worse prognosis in tumor patients . CNVs were also found to be associated with resistance to ICIs such as anti‐CTLA‐4 therapy in melanoma .…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of a subset of astrocytoma cases within The Cancer Genome Atlas (TCGA) glioma dataset showed similar results with mutual exclusivity between CDK4 and CDKN2A alterations in all except one case. IDH-mutant astrocytomas with either CDK4 amplifications or CDKN2A deletions had significantly shorter survival (median PFS of 32 months; median OS of 36 months) compared to IDH-mutant astrocytomas without these alterations (median PFS of 95 months, p = 0.02; median OS of >172 months, p = 0.02) [52]. The association of mutation or homozygous deletion of RB1 with shorter survival is not as well defined.…”
Section: Idh-mutant Lower-grade Astrocytomamentioning
confidence: 92%
“…Higher overall CNV correlated with worse prognosis within the IDH-mutant astrocytomas, irrespective of other histologic or genetic alterations. Cases with CDK4 amplification or CDKN2A deletion and poor outcomes tend to have elevated CNV [52], although a significant portion of cases with high CNV and poor outcome did not have evidence of CDK4 amplification or CDKN2A deletion [41,42], suggesting that these two measures may not be inextricably linked to one another. Measuring overall CNV appears to be a consistent and reproducible method for stratifying IDH-mutant astrocytomas.…”
Section: Idh-mutant Lower-grade Astrocytomamentioning
confidence: 97%
See 1 more Smart Citation